The Macroeconomics of Fiscal Policy Behavior in Liberia: An Error Correction Methodology - Tenny, Lester Zomatic (Archives of Business Research, 2022)
The debate of the size of government and economic growth has been popular especially in Africa. This study examined the relationship between fiscal variables, inflation and economic growth in Liberia. The Vector Error Correction Model (VECM) is employed. Results from the Impulse Response Function (IRF) analysis reveal that the response of inflation to growth in the Liberian economy over the study period, was weak, though significant and negative in the short run. However, it became positive and normalized in the medium and long runs. This means that inflation retarded growth only in the short run which is consistent with Barro (1996) empirical findings that inflation impact growth negatively and significantly. Also observed is the relationship between government expenditure and economic growth. For the Liberian economy and despite the interruption of the war, government expenditure impact on growth is a short run positive event, In medium to long run, it has a negative effect. This means that government expenditure only spur growth in the short run slightly but did not bring about growth in the medium to long run. This makes Keynesian theory relative to the intervention of government through spending given rise to growth invalid for the Liberian economy in the long run. However, the impact of growth on expenditure in the medium and long run is significant and strong. This suggests that indeed Wagner’s Law of increasing State spending is valid for the Liberian economy. Hence, fiscal policy is still a mix in stirring economic growth in Liberia. This study recommends well stirred fiscal policies that would positively impact on long run development in the Liberian economy